Determinants of wasting among children aged 2–5 years in Tanjung Priok, Jakarta, Indonesia - Herlinda Lizamona; Sandra Fikawati; Ruth Alpita Silva (AcTion: Aceh Nutrition Journal, 2025)
Wasting contributes to approximately 13% of the global child mortality. In 2022, the prevalence of wasting in Indonesia was 7,7%, declining from 10% in 2013. However, regions such as DKI Jakarta, particularly North Jakarta, still exhibit a high prevalence rate of 9,4%, indicating ongoing challenges in accessing adequate nutrition and healthcare services. This study aimed to examine the determinants of wasting in children aged 2–5 years. This cross-sectional study was conducted in Tanjung Priok, Jakarta, from June to July 2023. A total of 183 children, aged 2–5 years, were selected using purposive sampling. Data were collected through anthropometric measurements and structured interviews, using validated questionnaires covering dietary intake (SQ-FFQ), household socioeconomic status, and maternal nutrition knowledge. Data analysis included chi-squared tests and logistic regression analyses. The results showed that The prevalence of wasting was 8,7%. Although maternal nutrition knowledge was generally high, it was not significantly associated with wasting (p = 0,171). Energy (p = 0,023) and fat intake (p = 0,022) were significantly associated with wasting. Inadequate energy intake emerged as the dominant factor associated with a 3,7-fold increase in risk (p = 0,032). In conclusion, the primary determinant of wasting among children aged 2–5 years in Tanjung Priok is inadequate energy intake. Although most mothers had high nutrition knowledge, it did not significantly influence their wasting status. Therefore, interventions to prevent wasting should focus on improving energy and fat intake in children.